2000
DOI: 10.1046/j.1365-2206.2000.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Good lesbian, bad lesbian…’: regulating heterosexuality in fostering and adoption assessments

Abstract: The paper examines the assessment of lesbians who apply to foster or adopt, using data generated from 30 interviews with local authority social workers. Using feminist and queer theories, the author suggests that lesbian applicants pose a challenge to the discourse of ‘compulsory gender and heterosexuality’ which structures fostering and adoption work. It is argued that this discourse relies upon a series of assumptions about the automatic fitness of heterosexual applicants, especially concerning the idea of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 13 publications
3
53
1
2
Order By: Relevance
“…Perhaps the most substantial research conducted in the UK around gay and lesbian adoption and fostering, is that carried out by Hicks (1996Hicks ( , 1998Hicks ( , 2000Hicks ( , 2006aHicks ( b, 2008aHicks ( b, 2011Hicks ( , 2013, and Hicks and McDermott (1999). Building on the initial findings of Skeates and Jabri (1988), their work identified that gay and lesbian applicants were often associated with a degree of 'risk' and were closely scrutinised during assessment.…”
Section: Research With Gay and Lesbian Adopters And Foster Carersmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most substantial research conducted in the UK around gay and lesbian adoption and fostering, is that carried out by Hicks (1996Hicks ( , 1998Hicks ( , 2000Hicks ( , 2006aHicks ( b, 2008aHicks ( b, 2011Hicks ( , 2013, and Hicks and McDermott (1999). Building on the initial findings of Skeates and Jabri (1988), their work identified that gay and lesbian applicants were often associated with a degree of 'risk' and were closely scrutinised during assessment.…”
Section: Research With Gay and Lesbian Adopters And Foster Carersmentioning
confidence: 99%
“…Prior to recent social and legal changes, various empirical studies found that lesbians and gay men in the UK often faced overt or tacit discrimination when applying to become adopters or foster carers (Skeates and Jabri, 1988;Hicks, 1996Hicks, , 1998Hicks, , 2000Hicks, , 2011Hicks and McDermott, 1999). This occurred in numerous ways and at varying stages; from initial inquiries, to the home study assessment and finally as part of the approval panel.…”
Section: Research With Gay and Lesbian Adopters And Foster Carersmentioning
confidence: 99%
“…En este sentido, es preciso advertir que la legislación española en materia de adopción permite que las parejas casadas del mismo sexo adopten en igualdad de condiciones que las parejas heterosexuales 1 . En lo que respecta al proceso de adopción, algunas investigaciones (Hicks, 2000) advierten que en las entrevistas con las y los profesionales se reproducen esquemas heterosexuales como, por ejemplo, las preguntas que ahondan en una distribución genérica de las tareas domésticas. Esa ruptura con los esquemas binarios suscita dudas entre los y las evaluadoras acerca de las capacidades de las parejas del mismo sexo para criar y educar a menores.…”
Section: La Ruptura Con La Norma: Las Familias Formadas Por Parejas Dunclassified
“…En concreto, entre los 224 especialistas consultados en su estudio, un 77% se mostraba en contra basándose en las consecuencias negativas que tendría para la futura descendencia criarse en una unidad familiar de este tipo. Por otro lado, los prejuicios y estereotipos hacia las familias del mismo sexo que deciden adoptar también se han constatado en otras investigaciones desarrolladas en países del entorno latinoamericano (Herrera, 2009) y anglosajón (Hicks, 2000;Brooks y Goldberg, 2001;Brown et al, 2009). En este sentido, el miedo a la exclusión del proceso de adopción hace que algunas parejas adopten como personas solteras y oculten su relación de pareja (Gianino, 2008).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation